The Development of Interactive Media Based on Video Animation in the Use of a Total Station for Measurement Stake out the Building - Muhammad Bachrawi Luthfi; Sunar Rochmadi; Rihab Wit Daryono; Rozan Pajri Sandria Saputra (BIRCU, 2021)
This study aims to: (1) develop the concept of instructional media based on total station animation video which is used to measure building stake out; (2) developing interactive media designs; (3) due diligence of interactive media; and (4) dissemination of interactive media. This research is a research and development which refers to the 4D model. Non-test instruments with four-scale answer choices were used. The questionnaire was used in the expert validation process and the student's feasibility assessment. Data were analyzed quantitatively. The results of this research and development of instructional media conclude: (1) the concept of instructional media based on video animation of the total station is used to measure building stake out; (2) the initial media design consists of five main menus; (3) based on the assessment of instructional media by material experts it is categorized as